Integrating Medicinal Trees into Urban Landscape Planning: A Conservation Strategy for Biocultural Resilience in Riau - Samantha, Remiya (RUAS, 2026)
Medicinal trees are closely linked to the health system and Malay cultural heritage in Riau. However, the use of medicinal trees in urban green spaces remains limited, while urban landscapes are increasingly dominated by ornamental species that inadequately represent local ecological and cultural identity. This study aims to identify Malay medicinal tree species and formulate a conservation strategy based on biocultural resilience. The methods used were a literature review, an ethnobotanical survey, and multi-criteria analysis (MCDA). A total of 41 medicinal tree species were identified, including woody, fruit, and palm species. There are 6 priority species based on MCDA results: Artocarpus integer, Azadirachta indica, Cocos nucifera, Ficus sundaica, Ficus variegata, and Lagerstroemia indica. The Riau Urban Biocultural Landscape Framework integrates cultural values, ecological resilience, multifunctional landscape services, and urban identity as the basis for medicinal plant conservation and sustainable green infrastructure development.